2020
DOI: 10.1186/s13054-020-2798-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between furosemide administration and outcomes in critically ill patients with acute kidney injury

Abstract: Background: Although current guidelines for AKI suggested against the use of furosemide in AKI management, the effect of furosemide on outcomes in real-world clinical settings remains uncertain. The aim of the present study was to investigate the association between furosemide administration and outcomes in critically ill patients with AKI using real-world data. Methods: Critically ill patients with AKI were identified from the Medical Information Mart for Intensive Care (MIMIC)-III database. Propensity score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 32 publications
7
64
0
Order By: Relevance
“…Up to now, the main viewpoint is that diuretics including furosemide do not improve survival of AKI patients. The protective effect by improved renal function observed in some studies [1,4] (include Zhao's and ours) may be covered by the adverse events, such as electrolyte abnormalities [5]. Our study supports no benefit for furosemide on in-hospital mortality of AKI patients, despite a significant p value in the post-PSM dataset under the method of Cox regression (Table 1).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Up to now, the main viewpoint is that diuretics including furosemide do not improve survival of AKI patients. The protective effect by improved renal function observed in some studies [1,4] (include Zhao's and ours) may be covered by the adverse events, such as electrolyte abnormalities [5]. Our study supports no benefit for furosemide on in-hospital mortality of AKI patients, despite a significant p value in the post-PSM dataset under the method of Cox regression (Table 1).…”
supporting
confidence: 59%
“…We appreciate Dr. Wang and his colleagues for their comments on our recent article related to the association between furosemide use and outcomes in critically ill patients with AKI [1]. Using the eICU database, they found that furosemide use was associated with increased renal function recovery rate but not reduced in-hospital mortality.…”
Section: Authors' Responsementioning
confidence: 99%
See 1 more Smart Citation
“…KDIGO criteria are as follows [11]: increase in serum creatinine (SCr) to ≥1.5 times baseline must have occurred within the prior 7 days; or ≥0.3 mg/dl increase in SCr occurred within 48 h; or urine volume < 0.5 ml/kg/h for 6 h or more. The minimum of the SCr values available within the 7 days before admission was used as the baseline SCr [12,13]. When the preadmission SCr was not available, the rst SCr measured at admission was used as the baseline SCr [12,14].…”
Section: Study Populationmentioning
confidence: 99%
“…The minimum of the SCr values available within the 7 days before admission was used as the baseline SCr [12,13]. When the preadmission SCr was not available, the rst SCr measured at admission was used as the baseline SCr [12,14]. The diagnosis of type 2 diabetes was based on International Classi cation of Disease, Ninth Revision (ICD-9).…”
Section: Study Populationmentioning
confidence: 99%